Migration and Integration in a Post-Pandemic World Socioeconomic Opportunities and Challenges - Lerpold, Lin; Sjöberg, Örjan; Wennberg, Karl (Springer Nature, 2023)
As the world emerges from the COVID-19 pandemic, this book explores current migration and integration challenges. Against the background of long-term migration trends, it asks whether the pandemic has changed the patterns observed, transformed the circumstances international migrants face at destination or whether the opportunities and challenges for integration have been altered. Twenty-four researchers have contributed to this volume with research attention on how COVID-19 has affected transnationalism and identity, labour market employment, and impacted the discrimination of migrants in a variety of ways. Loyalties and tensions created by the need to include also hesitant migrant groups in vaccination programmes are explored. The role of cosmopolitanism and welfare chauvinism in narratives on inward migrations flows, the stance of trade unions on migration, the complexities of implementing return policies, and the challenges faced by unaccompanied refugee youth from Afghanistan are also discussed.